Kettlebell swing training improves maximal and explosive strength - Lake, J. P.; Lauder, M. A. (The Journal of Strength and Conditioning Research, 2012)
The aim of this study was to establish the effect that kettlebell swing (KB) training had on measures of maximum (half squat—HS—1 repetition maximum [1RM]) and explosive (vertical jump height—VJH) strength. To put these effects into context, they were compared with the effects of jump squat power training (JS—known to improve 1RM and VJH). Twenty-one healthy men (age = 18-27 years, body mass = 72.58 ± 12.87 kg) who could perform a proficient HS were tested for their HS 1RM and VJH pre- and post-training. Subjects were randomly assigned to either a KB or JS training group after HS 1RM testing and trained twice a week. The KB group performed 12-minute bouts of KB exercise (12 rounds of 30-second exercise, 30-second rest with 12 kg if <70 kg or 16 kg if >70 kg). The JS group performed at least 4 sets of 3 JS with the load that maximized peak power—Training volume was altered to accommodate different training loads and ranged from 4 sets of 3 with the heaviest load (60% 1RM) to 8 sets of 6 with the lightest load (0% 1RM). Maximum strength improved by 9.8% (HS 1RM: 165-181% body mass, p < 0.001) after the training intervention, and post hoc analysis revealed that there was no significant difference between the effect of KB and JS training (p = 0.56). Explosive strength improved by 19.8% (VJH: 20.6-24.3 cm) after the training intervention, and post hoc analysis revealed that the type of training did not significantly affect this either (p = 0.38). The results of this study clearly demonstrate that 6 weeks of biweekly KB training provides a stimulus that is sufficient to increase both maximum and explosive strength offering a useful alternative to strength and conditioning professionals seeking variety for their athletes.